Esophageal Atresia: Improved Outcome in High-Risk Groups Revisited - Malakounides, Georgina; Lyon, Paul; Cross, Kate; Pierro, Agostino; De Coppi, Paolo; Drake, David; Kiely, Edward; Spitz, Lewis; Curry, Joe (European Journal of Pediatric Surgery, 2016)
Objectives Improved survival in infants with esophageal atresia (EA) with a birth weight < 1,500 g or a major cardiac anomaly has been reported when compared with the original Spitz classification proposed in 1994.Aim We reviewed outcome data for infants born over the last decade in our institution to update previously reported survival statistics.Materials and Methods The records of all neonates (n = 200) with a diagnosis of EA managed in a single institution between 2001 and 2011 were reviewed and compared with data from the original Spitz study and the subsequent reported cohort from the same institution. Data were obtained on birth weight, presence of a major cardiac anomaly, and survival. Differences in survival were compared using the Yates-corrected chi-square test. Local ethical study approval was obtained.Results Infants born over the last decade had a comparable overall survival rate of 93% (186/200) versus 92.6% (174/188) in the previously reported cohort (1993–2004). We demonstrate an improved survival as compared to the Spitz cohort (87.6%, 326 /372, p = 0.06) and a statistically significant improvement in survival in Group II (p = 0.01). Within this group, 12/51 neonates had a birth weight < 1,500 g and 39/51 had major cardiac anomalies. Of interest, of the nine deaths in Group II, eight were in the subgroup with major cardiac anomalies.Conclusion The survival of neonates in Group II has significantly improved. Mortalities within this group were predominantly in the subgroup with major cardiac anomalies suggesting birth weight is of less significance than in previous years reflecting recent advances in neonatal care. We propose an updated prognostic classification that makes a distinction between cardiac and low-birth-weight infants.
Keywords: esophageal atresia; Spitz; survival; prognosis; classification